MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN MENEMPEL KARTU HURUF PADA ANAK USIA 4-5 TAHUN DI TK DARUSSALAMAH DESA PETAPAHAN JAYA KECAMATAN TAPUNG KABUPATEN KAMPAR - Hasanah, Dewi Nurul; Zulirfan, Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to The Ability To Know Alphabet in children aged 4-5 years through game to a letter in Kindergarten Darussalamah Petapahan Jaya Village District Tapung Regency Of Kampar. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years who are 16 children in Kindergarten Darussalamah. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that game a letter can boost ability to know a alphabet in children aged 4-5 years. It can be seen from the increase in the average percentage of the ability to know alphabet of children in the first cycle by 41,22% which is the criteria began to develop (MB) and an increase of 61,18% in the second cycle to 71,11% which is very good at developing criteria (BSB). So, game to a letter can improve ability to know alphabet of children aged 4-5 years in Kindergarten Darussalamah Petapahan Jaya Village District Tapung Regency Of KamparKeywords : The Ability To Know Alphabet, Game To A Letter